Determinant of Customer of Loyalty in Healthcare Industry : Mediating Role of Customer Trust - Endang Saefuddin Mubarok; Arif Kurniawan; Rahmat Hidayat; Ahman Kuktur Hia; Euis Bandawaty (Ilomata International Journal of Management, 2022)
This research aimed at understanding the effect of service quality, clinic image, and price/tariff on patient trust and loyalty. The multivariate analysis with descriptively and explanatorily-quantitative method was used for this research. The samples of the research were 120 respondents. Data collection was carried out using a questionnaire instrument and was subsequently analyzed by using Structural Equation Modeling (SEM). The results of this research concluded that the service quality and price/tariff had a significant effect on trust and clinic image had no significant effect on patient trust. The quality of service, clinic image, and price/tariff had a significant effect on patient loyalty, while trust had no significant effect on patient loyalty. Trust can mediate the effect of clinical image on patient loyalty. However, trust cannot mediate the effect of service quality and price/tariff on patient loyalty. The strength value of the dependent variable shown by the calculation of multiple correlation values (R2), both trust and patient loyalty are significant.